United in Diversity, Divided in Adversity? Support for Right-Wing Eurosceptic Parties in the Face of Threat Differs Across Nations - Vergani, Matteo; Bliuc, Ana-Maria; Stuart, Avelie; Badea, Constantina; Muntele, Daniela; McGarty, Craig (Frontiers in Psychology, 2019)
This article investigates whether the perceived threat of terrorism explains the support for right-wing Eurosceptic parties and Euroscepticism above and beyond other relevant variables, including economic and immigration perceived threats. We first examined the entire Eurobarometer samples of 2014 and 2015, and then conducted surveys in four EU countries, that is, UK (N=197), France (N=164), Italy (N=312), and Romania (N=144). Our findings suggest that the perceived terrorism threat is positively and significantly associated with negative views of the EU, as well as support for Eurosceptic parties in specific contexts (for example the UK), but the relationship between these variables varies across countries and it is less linear than we might expect.